Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I need help with this:

"Find all functions $f$, $g : \mathbb{Z} \rightarrow \mathbb{Z}$, with $g$ injective and such that: $$f(g(x)+y) = g(f(x)+y), \mbox{ for all } x, y \in \mathbb{Z}.$$

share|cite|improve this question
Did you mean all functions? – 1015 Feb 13 '13 at 18:46
italic bold YES – user62189 Feb 13 '13 at 19:20
A few random remarks: Notice that if we set $y=0$, we get $f(g(x))=g(f(x))$ for every $x\in\mathbb{Z}$. $f$ is injective: we can write every $x\in\mathbb{Z}$ as $g(0) + y$ for some $y = y(x)\in\mathbb{Z}$, and thus $f(x) = f(g(0) + y) = g(f(0)+y)$, and both $g$ and $y$ are injective. If there is some $x\in\mathbb{Z}$ with $n = f(x) = g(x)$, then we have $f(n+k)=f(g(x)+k)=g(f(x)+k)=g(n+k)$, and thus $f = g$. In this case, any injective $f:\mathbb{Z}\rightarrow\mathbb{Z}$ solves the problem, by setting $g=f$. – Daniel Robert-Nicoud Feb 13 '13 at 20:21

Suppose $f,g:\Bbb Z\to\Bbb Z$ with $g$ injective and $$f(g(x)+y)=g(f(x)+y)\tag{#}$$ for all $x,y\in\Bbb Z$.

Note that $$f(0)=f(g(x)-g(x))=g(f(x)-g(x))\tag{1}$$ for all $x$, so since $g$ is injective, then $f(x)-g(x)$ is constant. In particular, then $$f(x)=g(x)+c\tag{2}$$ for some $c\in\Bbb Z$. Note that it then follows that $f$ is injective.

It follows from $(1)$ and $(2)$ that $$g(c)=g(f(x)-g(x))=f(0)=g(0)+c.$$ Suppose $g(x+c)=g(x)+c$ for some $x\in\Bbb Z$. Then $$g(x+1+c)=g(f(0)-g(0)+x+1)=f(g(0)-g(0)+x+1)=f(x+1)=g(x+1)+c,$$ and similarly, $$g(x-1+c)=g(x-1)+c.$$ By $2$-directional induction on $x$, we have $$g(x+c)=g(x)+c\tag{3}$$ for all $x\in\Bbb Z$. Using $(3)$, another quick $2$-directional induction on $m$ will show that $$g(y+mc)=g(y)+mc\tag{4}$$ for all $m,y\in\Bbb Z.$

Now, if $c=0$, then we must have $f=g$ by $(2)$. Suppose $c\neq 0$. Given any $x\in\Bbb Z$, there is a unique $0\leq y<|c|$ such that $x=y+mc$ for some $m\in\Bbb Z$ (why?)--denote this $y$ by $r(x)$--so by $(4)$, we have $$g(x)=g(r(x)+mc)=g(r(x))+mc=g(r(x))+x-r(x),$$ so $$g(x)-x=g(r(x))-r(x).$$ Defining $h(x):=g(x)-x$, we have $$h(x)=h(r(x))\tag{5}$$ for all $x\in\Bbb Z$. Observing that $r(x+mc)=r(x)$ for all $x,m\in\Bbb Z$ (why?), it follows that $h$ is a periodic function $\Bbb Z\to \Bbb Z$, with $c$ a period of $h$.

The above gives us necessary conditions for $f,g$ to satisfy. We will see that they are sufficient, as well. Specifically, we prove the following:

Claim: Suppose $f,g:\Bbb Z\to\Bbb Z$ with $g$ injective. Then $f,g$ satisfy $(\#)$ if and only if one of the following holds:

(a) $f=g$, or

(b) there is some non-$0$ $c\in\Bbb Z$ and some periodic function $h:\Bbb Z\to\Bbb Z$ such that $h$ has $c$ as a period, $g(x)=h(x)+x$, and $f(x)=g(x)+c$ for all $x\in\Bbb Z$.

Proof: We saw above that if $f,g$ satisfy $(\#)$, then (a) or (b) holds. If (a) holds, then it's easily seen that $f,g$ satisfy $(\#)$, so suppose that (b) holds. Then $$\begin{align}f(g(x)+y) &= g(g(x)+y)+c\\ &= h(g(x)+y)+g(x)+y+c\\ &= h(g(x)+y+c)+g(x)+y+c\\ &= g(g(x)+y+c)\\ &= g(g(x)+c+y)\\ &= g(f(x)+y),\end{align}$$ as desired. $\Box$

share|cite|improve this answer

How about $f(x)=g(x)=x?$......

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.